1995
DOI: 10.1007/bf00170155
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular effects of selective agonists and antagonists of histamine H3 receptors in the anaesthetized rat

Abstract: The cardiovascular responses to a series of selective histamine H3 receptor agonists, (R) alpha-methylhistamine, imetit and immepip and selective antagonists, thioperamide, clobenpropit and clophenpropit, were studied in anaesthetized rats. At 0.003-1 mumol/kg i.v. doses, H3 agonists failed to produce any significant change in the basal blood pressure and heart rate. Larger doses of (R) alpha-methylhistamine increased the blood pressure and heart rate and higher doses of imetit caused vasodepressor responses a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…In fact, in agreement with the lack of effect of immepip on the methoxamine-induced vasopressor response (Fig. 1), Coruzzi et al, 1995 showed in anaesthetized rats that, unlike R-(-)-α-methylhistamine and imetit, immepip did not significantly change basal blood pressure and heart rate. In contrast, R-(-)-α-methylhistamine has been reported to produce a direct vasopressor response in pithed rats, which is not mediated by histamine H 1 , H 2 or H 3 receptors (Malinowska and Schlicker, 1991).…”
Section: Changes On Systemic Haemodynamic Variables Produced By the Dsupporting
confidence: 87%
“…In fact, in agreement with the lack of effect of immepip on the methoxamine-induced vasopressor response (Fig. 1), Coruzzi et al, 1995 showed in anaesthetized rats that, unlike R-(-)-α-methylhistamine and imetit, immepip did not significantly change basal blood pressure and heart rate. In contrast, R-(-)-α-methylhistamine has been reported to produce a direct vasopressor response in pithed rats, which is not mediated by histamine H 1 , H 2 or H 3 receptors (Malinowska and Schlicker, 1991).…”
Section: Changes On Systemic Haemodynamic Variables Produced By the Dsupporting
confidence: 87%
“…Conflicting results are seen concerning the prejunctional effects of H3-receptors in the rat, with some studies reporting a lack of action [4] and others an inhibition of electrically evoked noradrenaline release [ 141 and vasopressor response [MI. It has been suggested that prejunctional H3-receptors are functionally inactive under basal conditions in the rat [13]. Our results show that they also appear to play a minor role on noradrenaline release in the context of myocardial ischaemia in this species.…”
Section: Stimulation Of H-receptors Present On Sympatheticsupporting
confidence: 46%
“…Basal cardiovascular effects of H 3 agonists vary according to the species. In the guinea‐pig and in the rabbit, R‐α‐methyl‐histamine induces bradycardia and hypotension ( McLeod et al ., 1994 ) while in the rat, H 3 agonists have no effects ( Corruzzi et al ., 1995 ) at least not at the doses where they are selective for H 3 ‐receptors. Our results show that, in the dog, H 3 ‐receptor activation by BP 2.94 decreased heart rate and tended to reduce contractility and arterial pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that, in the dog, H 3 ‐receptor activation by BP 2.94 decreased heart rate and tended to reduce contractility and arterial pressure. H 3 ‐antagonists fail to induce cardiovascular effects in the guinea‐pig, rabbit and rat ( Corruzzi et al ., 1995 ). We observed that, in the dog, SC 359 induced an important vasopressive response and a tachycardia after R‐α‐methyl‐histamine or BP 2.94.…”
Section: Discussionmentioning
confidence: 99%